Conclusion: What We Learned and Next Steps - Haythorn, Trace (Journal of pastoral care & counseling, 2021)
In the previous articles, my colleagues have presented analyses of the survey data that have implications for professional preparation, practice and ongoing professional development. I will conclude this volume highlighting six areas that require further investigation, theoretical development and practical integration.